Attitudes of Bidayuhs in Bau district towards introduction of Bidayuh language in schools - Phang, Dennis Phillipson (University Malaysia Sarawak, UNIMAS., 2009)
This study was carried out to determine the attitude of Bidayuh towards introduction of Bidayuh Language in schools. With the knowledge of their attitudes, then it will be easier to predict and regulate their behavior in support for their mother tongue to be introduced in schools, and making a positive step towards revitalizing and maintaining their heritage language. As such, this study aims to find out the attitudes of Bidayuhs in Bau district using four components of attitude; cognitive, affective, behavioral and integrative and instrumental orientation, and to find out if there is any differences in attitudes from different age and academic level. For this purpose, a total of 200 respondents from Bau district in Kuching, Sarawak which comprises of three groups according to their age are studied. The research design of this study is survey and questionnaires were distributed among the Bidayuhs in Bau in order to gain their attitude based on various components of attitude, namely cognitive, affective, behavioral and integrative and instrumental orientation. Findings from this study were analysed using SPSS Version 14 to discover significance difference in attitudes of the Bidayuhs. Generally, the Bidayuhs in Bau district are positive and in support towards the introduction of Bidayuh language in schools, regardless of age or academic status. There is also no significant difference in opinions according to the four components of attitudes, from different age and different academic level. As such, due to the positive attitudes and support from the community, the significant of introducing the Bidayuh language as a subject in schools should be considered seriously by policy makers to further enhance the racial identity among the people in the community.